Synergistic effect of photobiomodulation and leukocyte-platelet rich fibrin on bone regeneration in rat critical defects - Sadeghian, Ali; Rohani, Bita; Hasannia, Sadegh; Mashhadiabbas, Fatemeh; Fekrazad, Reza (Photodiagnosis and photodynamic therapy, 2025)
•The groups of rats that underwent photobiomodulation therapy (PBMT) exhibited enhanced and expedited healing of soft tissue relative to the groups that did not receive PBMT following surgical intervention.•The integration of leukocyte and platelet-rich fibrin (LPRF) with photobiomodulation (PBM) markedly improves new bone formation in critical calvarial bone defects in rats, surpassing the efficacy of treatments involving bone material combined with either normal saline, LPRF alone, or normal saline with PBM.•The synergistic application of LPRF and photobiomodulation may offer an effective strategy for improving bone regeneration in clinical settings. This study aimed to evaluate the effects of leukocyte and platelet-rich fibrin (LPRF) and LPRF combined with photobiomodulation therapy (PBMT/LPRF) on bone regeneration in critical-sized defects. Forty-six male Wistar rats, weighing 200 ± 20 g, aged 9 weeks ± 2, were randomly assigned to four groups: (1) bone material with normal saline referred to as Control, (2) bone material with LPRF, referred to as BL, (3) bone material with LPRF and PBMT referred to as BLP, and (4) bone material with normal saline and PBMT referred to as BP. Bone defects of 8 mm were created in the calvaria using a trephine bur under anesthesia. Bone graft material mixed with normal saline or LPRF was applied to the defect sites, followed by coverage with a collagen membrane. The PBMT groups received laser treatment (WL:810 nm, Irradiation mode: CW,P:200 mW, ED:8 J/cm², Spot size:0.5 cm², Total dose:96 J/cm²) . All groups were evaluated after 30 days for histological analysis of bone regeneration, inflammatory response and soft tissue healing. The study included forty-six subjects across four groups: BLP (23.9%), BL (23.9%), Control (26.1%), and BP (26.1%). Connective tissue analysis revealed that BL and BLP groups had 81.8% loose connective tissue, while the Control group had 91.7% loose connective tissue and 8.3% fibrosis. Moreover, the BP group had 58.3% of subjects showing loose connective tissue, 33.3% forming granulation tissue, and 8.3% developing fibrosis. Additionally, in the BP group, other tissues such as normal connective tissue were also present, though in smaller proportions. In terms of scaffold remaining and new bone generation, the BL group had 45.45% (SD = 22.67) scaffold and 7.29% (SD = 2.77) new bone. The BLP group showed higher scaffold remaining (46.09%, SD = 17.91) and significantly more new bone (16.61%, SD = 9.08). The Control group had a scaffold remaining of 54.21% (SD = 21.41) and new bone generation of 6.84% (SD = 2.32). The BP group exhibited the highest scaffold remaining (61.03%, SD = 15.13) but lower new bone generation (6.73%, SD = 2.77). Moreover, the groups receiving PBMT exhibited enhanced and accelerated soft tissue healing during the initial three weeks. Results of the present study proved that PBMT with LPRF expresses significant bone regeneration in critical-sized defects than each treatment performed separately when compared to those from the control group, however, this benefit needs to be confirmed with larger sample sizes and longer follow-ups.